MECHANICAL PROPERTIES OF HONEYCOMB STRUCTURED ZR-BASED BULK METALLIC GLASS SPECIMENS FABRICATED BY LASER POWDER BED FUSION - Wegner, J.; Frey, M.; Stiglmair, P; Kleszczynski, S; Witt, G; Busch, R (The South African Journal of Industrial Engineering, 2019)
Laser powder bed fusion of bulk metallic glasses offers great potential to overcome the existing restrictions of the geometrical size and complexity of bulk metallic glasses in conventional manufacturing routes due to high cooling rates during laser powder bed fusion. Bulk metallic glasses exhibit extraordinary strength, paired with high elasticity. Yet insights into additive manufactured bulk metallic glasses, especially of complex structures, are limited. The present article investigates the mechanical behaviour of Zr-based bulk metallic glasses, fabricated into honeycomb structures through laser powder bed fusion, by performing three-point bending tests. The results reveal a significant increase in specific strength, quasi-plasticity, and high elastic elongation. These structures thus offer great potential for light-weight applications and compliant mechanisms.